Engineering Promiscuous Alcohol Dehydrogenase Activity of a Reductive Aminase AspRedAm for Selective Reduction of Biobased Furans - Jia, Hao-Yu; Yang, Zi-Yue; Chen, Qi; Zong, Min-Hua; Li, Ning (Frontiers in Chemistry, 2021)
Catalytic promiscuity is a promising starting point for improving the existing enzymes and even creating novel enzymes. In this work, site-directed mutagenesis was performed to improve promiscuous alcohol dehydrogenase (ADH) activity of reductive aminase from Aspergillus oryzae (AspRedAm). AspRedAm showed the cofactor preference toward NADPH in reductive aminations, while it favored NADH in the reduction reactions. Some key amino acid residues such as N93, I118, M119, and D169 were identified for mutagenesis by molecular docking. Variant N93A showed the optimal pH and temperature of 8 and 30 °C, respectively, in the reduction of 5-hydroxymethylfurfural (HMF). The thermostability was enhanced upon mutation of N93 to alanine. The catalytic efficiency of variant N93A (kcat/Km, 23.6 mM-1 s-1) was approximately 2-fold higher compared to that of the WT enzyme (13.1 mM-1 s-1). The improved catalytic efficiency of this variant may be attributed to the reduced steric hindrance that stems from the smaller side chain of alanine in the substrate-binding pocket. Both the WT enzyme and variant N93A had broad substrate specificity. Escherichia coli (E. coli) cells harboring plain vector enabled selective reduction of biobased furans to target alcohols, with the conversions of 35-95% and the selectivities of >93%. The introduction of variant N93A to E. coli resulted in improved substrate conversions (>98%) and selectivities (>99%).